An Analysis of Elementary School Students’ Character Building through The Pancasila Student Profile Strengthening Project - Syarifah Fadillah; Mai Yuliastri Simarmata; Dwi Fajar Saputri (STAI Hubbulwathan Duri, 2023)
The Pancasila student profile refers to the development of character and abilities within a school setting, which includes the implementation of the Pancasila student profile strengthening initiative. This study seeks to provide a description of the outcomes of implementing the Pancasila student profile strengthening project, specifically focusing on promoting a sustainable lifestyle to develop three dimensions: (1) fostering faith, devotion to God, and noble character in relation to both moral values towards nature and personal conduct, (2) encouraging creativity in terms of generating original works and actions, and (3) promoting collaboration among students. This study employs Research and Development methodologies. The data for this study was collected from a sample of 4 teachers and 120 children in grade 4 at an elementary school in Pontianak. The findings indicated that the activities conducted by students during their involvement in the Pancasila student profile strengthening project have the capacity to develop the character or competency of the third Pancasila student profile in those specific aspects.